2017
DOI: 10.1002/prp2.361
|View full text |Cite
|
Sign up to set email alerts
|

Daikenchuto (TU‐100) alters murine hepatic and intestinal drug metabolizing enzymes in an in vivo dietary model: effects of gender and withdrawal

Abstract: Herbal medicines and natural products used for maintenance of health or treatment of diseases have many biological effects, including altering the pharmacokinetics and metabolism of other medications. Daikenchuto (TU‐100), an aqueous extract of ginger, ginseng, and Japanese green pepper fruit, is a commonly prescribed Kampo (Japanese herbal medicine) for postoperative ileus or bloating. The effects of TU‐100 on drug metabolism have not been investigated. In this study, we analyzed the effect of TU‐100 on expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…We noted strong sex differences among the groups even after the mixed bedding protocol was instituted, suggesting that sex is a strong independent host factor driving gut microbial assemblage. This finding emphasizes the importance of analyzing both female and male animals separately in all gut microbiome studies, as these differences could cause differential effects in the host, e.g., the development of the immune system ( Brown, Sadarangani & Finlay, 2013 ; Gensollen et al, 2016 ) or in host xenobiotic metabolism ( Claus et al, 2011 ; Meinl et al, 2009 ; Nobutani et al, 2017 ). In light of well-established differences in treatment regimens and drug toxicity among male and female human subjects ( Soldin & Mattison, 2009 ), inclusion of both sexes in studies examining gut microbes is now encouraged by the National Institutes of Health and other funding agencies.…”
Section: Discussionmentioning
confidence: 93%
“…We noted strong sex differences among the groups even after the mixed bedding protocol was instituted, suggesting that sex is a strong independent host factor driving gut microbial assemblage. This finding emphasizes the importance of analyzing both female and male animals separately in all gut microbiome studies, as these differences could cause differential effects in the host, e.g., the development of the immune system ( Brown, Sadarangani & Finlay, 2013 ; Gensollen et al, 2016 ) or in host xenobiotic metabolism ( Claus et al, 2011 ; Meinl et al, 2009 ; Nobutani et al, 2017 ). In light of well-established differences in treatment regimens and drug toxicity among male and female human subjects ( Soldin & Mattison, 2009 ), inclusion of both sexes in studies examining gut microbes is now encouraged by the National Institutes of Health and other funding agencies.…”
Section: Discussionmentioning
confidence: 93%
“…Our recent report using the same murine model demonstrated that dietary TU-100 modulates the transcript and protein expression of drug metabolizing enzymes and drug transporters in the liver, small intestine, and colon in a dose- and sex-dependent manners and that in most cases the effects were reversible after cessation of TU-100 treatment [ 34 ]. Taken together, our results show an interactive network between consumption of TU-100, alterations of gut microbiota, and changes in host xenobiotic metabolism.…”
Section: Resultsmentioning
confidence: 99%
“…Also noteworthy is that sex-specific differences have been reported both with respect to the gut microbiota [ 31 , 32 ] and also with respect to drug metabolism [ 33 ]. We recently reported that long-term consumption of TU-100 affects murine hepatic and intestinal drug metabolizing enzymes [ 34 ]. Collectively these findings suggest that the gut microbiota can mediate some of the actions of TU-100 and that more information is needed to understand how greater efficacy and dosing of TU-100 can be achieved.…”
Section: Introductionmentioning
confidence: 99%
“…This finding emphasizes the importance of analyzing both female and male animals separately in all gut microbiome studies, as these differences could cause differential effects in the host, e.g. the development of the immune system (Brown et al 2013;Gensollen et al 2016) or in host xenobiotic metabolism (Claus et al 2011;Meinl et al 2009;Nobutani et al 2017). In light of well-established differences in treatment regimens and drug toxicity among male and female human subjects (Soldin and Mattison 2009), inclusion of both sexes in studies examining gut microbes is now encouraged by the National Institutes of Health and other funding agencies.…”
Section: Discussionmentioning
confidence: 99%